A Review of Big Data in Network Intrusion Detection System: Challenges, Approaches, Datasets, and Tools - Alshamy, Reem; Ghurab, Mossa (International Journal of Computer Sciences and Engineering, 2020)
Intrusion Detection System (IDS) is a promised research field in the cybersecurity due to the rapid development of the Internet. Many IDS employ classification algorithms for classifying network traffic, and these classification algorithms failed to achieve accurate attack detection due to the huge amount of data. However, by applying dimensional reduction, data can be efficiently reduced and achieve accurate attack detection. The main work in this paper is to provide a comprehensive review of the IDS types and methods used to detect attack, advantages and disadvantages of each type. Furthermore, the authors focus on the Network Intrusion Detection System (NIDS) type and introduce the ten characteristics of Big Data and the challenges of Big Data in NIDS. Furthermore, we analyze different approaches used in NIDS based on machine learning algorithms, for each approach we study the performance of classifiers (Binary or Multi classification) under eight datasets and dimensional reduction techniques. A comparison of some machine learning algorithms and the five tools used for analyzing Big Data are presented. Discussions came from our analysis of current research. Finally, we will finish this paper by representing conclusions and describe future work.